Theory and Practice in Aircraft Financial Evaluation. - Gibson, William E.; Morrell, Peter (Elsevier, 2004)
This paper explores the state of practice regarding aircraft financial evaluation. Traditional measures of aircraft economic viability, including Direct Operating Cost (DOC) comparison, ignore both the non-cash elements of costs, and the time value of money. Practitioners adopting more advanced techniques often go straight to the Net Present Value calculation using an “industry standard” discount rate, ignoring critical problems such as estimating the cost of capital, quantifying the highly uncertain economic environment airlines face, and valuing the flexibility offered by manufacturer options and operating leasing. We propose taking advantage of the potential flexibility of the NPV approach by close attention to the choice of discount rates to flesh out investment/financing interactions, use of Monte Carlo analysis to quantify risk up front, and Real Options Analysis (ROA) to better understand the value of flexibility to aircraft operators.